Comparing Symptoms of Post-Polio Syndrome in Athlete and Non-Athlete Poliomyelitis Survivors - Shaghayegh Sayyar; Hasan Daneshmandi; Fateme Ebrahimi (Physical Treatments, 2017)
Purpose: Long term effects of poliomyelitis are known in many countries. Despite no definite label for these signs and symptoms, there is a remarkable similarity among patients with regard to description of the problems and complications of the disease. In this study, we compared the prevalence of symptoms of Post-Polio Syndrome (PPS) in athlete and non-athlete poliomyelitis survivors. Methods: This is a causal-comparative study. The statistical population consisted of all people who had polio in Kerman Province. Of them, 28 people (9 males and 19 females) with the mean(SD) age of 36.61(8.23) years were purposefully selected as the study samples and were grouped in athlete and non-athlete samples. The athlete group comprised 15 people with an mean(SD) age of 34.62(9.42) years who were engaged in physical activities, including swimming, table tennis and sitting volleyball, 3 times a week (on average) during the last year. The non-athlete group also consisted of 15 people with an mean(SD) age of 6.91(38.33) years who didn’t do any regular physical activity during this time. With respect to the major indexes of PPS, the symptoms of this syndrome were examined using quality of life questionnaire (SF-36), Fatigue Severity Scale (FSS), and McGill pain questionnaire to evaluate mental and physical function, fatigue and muscular pain, respectively in the study groups. The obtained data were analyzed using descriptive statistics, the Pearson correlation coefficient and Independent t test with SPSS V-22. The significance level was set at P≤0.05. Results: The results indicate a high prevalence rate of PPS syndrome including main symptoms of pain and fatigue (57.53%). Results also support a significant difference between the physical health of athlete and non-athlete groups (P=0.02), while no significant difference was observed between these two groups with respect to their mental health status. Also, there was a significant difference between the athlete and non-athlete people in terms of the fatigue (P=0.04) and pain intensity (P=0.04). Moreover, there was a significant relationship between the age at the first attack of polio and fatigue (r=0.59) and physical health (r=0.69), while there was no significant relationship between the age at the first attack of the disease and pain (r=0.24) and mental health (r=-0.09). Conclusion: Regular physical activity can help patients with a history of polio achieve higher level of health and lower level of functional impairments. Improving the physical condition of these patients through training programs can play an important role in improving their quality of life.